1998
DOI: 10.1207/s15327736me1102_2
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Corporate Newspaper Structure and Profit Making

Abstract: A national probability survey of newspapers conducted in 1993 found that the more a newspaper exhibits the characteristics of the corporate form of organization, the less emphasis it places on profits as an organizational goal and the more emphasis it places on product quality and other nonprofit goals. However, another survey conducted in the fall of 1996 failed to support the profit findings. The study detailed in this article was conducted in 1997 in an attempt to resolve the discrepancy. Corporate newspape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Breaking with previous theorists, Demers (1996aDemers ( , 1998b has argued that a positive correlation between managerial control and high profit rates is compatible with the managerial revolution thesis. The corporate form of organization-which he defines as a complex bureaucracy with a high degree of managerial control 2 -is structurally organized to maximize profits, but it is expected to place less emphasis on profits as an organizational goal.…”
Section: Empirical Research On Corporate Newspapersmentioning
confidence: 81%
See 2 more Smart Citations
“…Breaking with previous theorists, Demers (1996aDemers ( , 1998b has argued that a positive correlation between managerial control and high profit rates is compatible with the managerial revolution thesis. The corporate form of organization-which he defines as a complex bureaucracy with a high degree of managerial control 2 -is structurally organized to maximize profits, but it is expected to place less emphasis on profits as an organizational goal.…”
Section: Empirical Research On Corporate Newspapersmentioning
confidence: 81%
“…The corporate form of organization-which he defines as a complex bureaucracy with a high degree of managerial control 2 -is structurally organized to maximize profits, but it is expected to place less emphasis on profits as an organizational goal. As noted earlier, several national probability samples of daily newspapers in the United States support this argument (Demers, 1996a(Demers, , 1996c(Demers, , 1998b. Corporate newspapers are more profitable, Demers argued, because they benefit from economies of scale and superior management and human resources.…”
Section: Empirical Research On Corporate Newspapersmentioning
confidence: 89%
See 1 more Smart Citation
“…So, they will effectively foreclose market entry and new entrants will barely make a profit on product differentiation; therefore, the strategy of increasing product diversity through new entrants does not apply for high concentration markets. Moreover, some studies found that incumbents in high concentration markets, while serving the majority of customers, take into account the development of product diversity [12,16]. Chipty [17] found that consumers in a monopolistic competitive market are not better off, and no worse off, than those in a market with low concentration in terms of consumer welfare, such as product diversity.…”
Section: The Relationship Between Market Competition and Diversity Ofmentioning
confidence: 99%
“…Chipty [17] found that consumers in a monopolistic competitive market are not better off, and no worse off, than those in a market with low concentration in terms of consumer welfare, such as product diversity. Demers [16] also suggested that in the newspaper industry, incumbents will place emphasis on differentiating themselves through being more innovative and allowing reporters more autonomy.…”
Section: The Relationship Between Market Competition and Diversity Ofmentioning
confidence: 99%